Адміністративне оскарження актів у справах про фінансову відповідальність - Шумейко, Іван Павлович; Shumeiko, Ivan (Cуми : СНАУ, 2025)
UA: У статті надано характеристику адміністративному оскарженню актів у справах про фінансову відповідальність в Україні. З’ясовано, що правовідносини у цій сфері врегульовані загальними нормами Закону України «Про адміністративну процедуру» (крім відносин у сфері захисту економічної конкуренції) та нормами спеціального законодавства, передусім податкового. Визначено, що правила щодо строку оскарження передбачають його відлік з моменту доведення акта до відома особи або з моменту прийняття акта, а строк обчислюється у робочих, календарних днях або дорівнює місяцю. Наголошено на тому, що право на адміністративне оскарження має адресат адміністративного акта, а також потерпілий, якщо такий бере участь у провадженні. Зазначено, що процедура адміністративного оскарження складається з трьох стадій. Визначено, що на першій стадії з’ясовується наявність чи відсутність перешкод до початку провадження. На другій стадії суб’єкт розгляду скарги, керуючись принципом офіційності, вчиняє підготовчі дії, в тому числі шляхом збирання і забезпечення доказів за власною ініціативою. Обґрунтовано, що третя стадія є розглядом скарги по суті, який в разі утворення комісії з розгляду скарг здійснюється в усному провадженні. З’ясовано, що процедура закінчується ухваленням рішення або автоматичним задоволенням скарги в силу факту спливу строку розгляду скарги (якщо це передбачено законом). Зазначено, що за результатами адміністративного оскарження акту у справі про фінансову відповідальність може бути прийнято рішення про залишення скарги без задоволення або про повне чи часткове задоволення скарги. В останньому випадку оскаржений акт підлягає повному чи частковому скасуванню або зміні. Визначено, що в разі скасування акта може бути призначено новий розгляд справи або прийнято рішення про закриття справи; крім того, може бути вирішено питання про відшкодування заподіяної шкоди. Виявлено, що винятковим наслідком адміністративного оскарження у справах про фінансову відповідальність є погіршення правового становища особи, яка подала скаргу; обґрунтовано необхідність відмови від цього підходу з огляду на порушення права на захист. EN: The article provides a description of administrative appeals against acts in cases concerning financial responsibility in Ukraine. It has been established that legal relations in this area are regulated by the general provisions of the Law of Ukraine ‘On Administrative Procedure’ (except for relations in the field of economic competition protection) and the provisions of special legislation, primarily tax legislation. It is determined that the rules regarding the time limit for appeal provide for its calculation from the moment the act is brought to the attention of the person or from the moment the act is adopted, and the time limit is calculated in working days, calendar days or is equal to one month. It is emphasised that the right to administrative appeal is held by the addressee of the administrative act, as well as the injured party, if such a party participates in the proceedings. It is noted that the administrative appeal procedure consists of three stages. It has been established that the first stage involves determining the presence or absence of obstacles to the commencement of proceedings. It is determined that at the second stage, the subject of the complaint, guided by the principle of officiality, takes preparatory actions, including by collecting and securing evidence on its own initiative. It is determined that the third stage is the consideration of the complaint on its merits, which, in the case of the formation of a commission for the consideration of complaints, is carried out in oral proceedings. It has been established that the procedure ends with the adoption of a decision or the automatic satisfaction of the complaint due to the expiry of the deadline for considering the complaint (if provided for by law). It is noted that, based on the results of an administrative appeal against an act in a case concerning financial responsibility, a decision may be made to dismiss the complaint or to satisfy it in whole or in part. In the latter case, the contested act is subject to full or partial cancellation or amendment. It is determined that in the event of cancellation of the act, a new consideration of the case may be appointed or a decision to close the case may be made; in addition, the issue of compensation for the damage caused may be resolved. It has been found that an exceptional consequence of administrative appeals in cases of financial responsibility is the deterioration of the legal position of the person who filed the complaint; the need to abandon this approach is justified in view of the violation of the right to defence.
Administrative appeal against acts in cases concerning financial responsibility
Keywords: адміністративне оскарження; адміністративний акт; заборона повороту до гіршого; зупинення дії акта; комісія з розгляду скарг; принцип офіційності; строк оскарження; фінансова відповідальність; administrative act; administrative appeal; appeal period; complaints commission; financial responsibility; principle of officiality; prohibition of reversal for the worse; suspension of the act